(untitled) (Periodicals of Engineering and Natural Sciences, 2021)
In this paper another fundamental change in particular SEE change was applied to address straight normal deferential conditions with consistent coefficients and SEE change of incomplete derivative is inferred and its appropriateness showed utilizing three is inferred and its appropriateness showed utilizing: wave equation, heat equation and Laplace equation, we find the particular solutions of these equations.